Emotional and behavioral disorders in a 6th grader and their implications for EFL teachers on classroom management at Unidad Educativa Santiago Mayor during the first quinmester 2019-2020. - Araujo Zapata, Doménica Soledad (2020)
This is the study of behavioral and emotional disorders (BED) in a child at a high school of Guayaquil which helps to understand the implications for English teachers. This research was conducted in order to recognize negative situations which are produced by students with BED. Emotional and Behavioral Disabilities are related to the persistent mood changes on children, which provoke them to start incidents inside of the classroom. EFL Teachers at Unidad Educativa Santiago Mayor, answered a survey in order to collect data about students with emotional and behavioral disorders. It was also applied a structured interview to a psychologist and an unstructured interview to the classroom teacher of a child with bipolar disorder. The results of the survey showed that there is a need for training programs, while the interviews provided important information about the implications for EFL teachers to be used in classroom management strategies.